Investigations on the role of a lysozyme from the malaria vector Anopheles dirus during malaria parasite development - Parichat Lapcharoen (2018)
A cDNA encoding a lysozyme was obtained by rapid amplification of cDNA ends-polymerase chain reaction (RACE-PCR) from females of the malaria vector Anopheles dirus A (Diptera: Culicidae). The 623. bp lysozyme (AdLys c-1) cDNA encodes the 120 amino acid mature protein with a predicted molecular mass of 13.4. kDa and theoretical pI of 8.45. Six cysteine residues and a potential calcium binding motif that are present i n AdLys c-1 are highly conserved relative to those of c-type lysozymes found in other insects. RT-PCR analysis of the AdLys c-1 transcript revealed its presence at high levels in the salivary glands both in larval and adult stages and in the larval caecum. dsRNA mediated gene knockdown experiments were conducted to examine the potential role of this lysozyme during Plasmodium berghei infection. Silencing of AdLys c-1 resulted in a significant reduction in the number of oocysts as compared to control dsGFP injected mosquitoes. © 2011 Elsevier Ltd.